Analisis Tingkat Literasi Lingkungan Media Sosial Pada Mahasiswa Unimed Pengguna Instagram Dan Tiktok - Cika Mufida Siregar; Mahfuzi Irwan; Putri Dia Sakina; Sabrina Maharani Putri (Didakta Nusantara: Journal of Education and Learning, 2026)
This research investigates the level of social media literacy among Generation Z students who actively use Instagram and TikTok. The study aims to identify how students understand, analyze, and verify information before sharing it on social media platforms. A descriptive quantitative method was applied, and the data were collected through a Likert-scale questionnaire distributed to 50 university students aged 18–24. The findings show that the majority of respondents demonstrate a high level of social media literacy, as indicated by strong preferences in the categories of Agree and Strongly Agree. These results imply that students tend to be more critical and selective when evaluating online information, indicating their awareness of misinformation risks. The study concludes that Generation Z users are generally capable of practicing responsible digital behavior. Further educational support is recommended to strengthen critical literacy skills, particularly in identifying manipulated content and biased information, to create a healthier digital ecosystem